Development of speech recognition using Matlab / Tuan Ida Syarmila Tuan Mustafa - Tuan Mustafa, Tuan Ida Syarmila (2000)
This project paper provides an overview of the recent developments in the area of speech processing and in particular in the field of speech recognition. This project paper will present the results of an ongoing work in using Matlab for speech recognition to identify the words spoken by a user. The data used are words 'SAYA' and 'NAMA SAYA IDA'. These words were recorded using spectra software and export to the Matlab. Matlab is used to recognize the user by comparing the real user's voice waveform and the waveform that recognized by Matlab.